2020
DOI: 10.1038/s41598-020-58341-8
|View full text |Cite
|
Sign up to set email alerts
|

Phlobaphenes modify pericarp thickness in maize and accumulation of the fumonisin mycotoxins

Abstract: phlobaphenes are insoluble phenolic compounds which are accumulated in a limited number of tissues such as seed pericarp and cob glumes, conferring on them a typical red-brown pigmentation. These secondary metabolites, derived from 3-deoxy flavonoids, are thought to have an important role in plants' resistance against various pathogens, e.g. by reducing fungal infection, and also to have beneficial effects on human and animal health due to their high antioxidant power. The aim of this work was to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…Because phlobaphene pigment accumulation is correlated with kernel pericarp thickness and reduced mycotoxin contamination on maize kernels (Landoni et al 2020), the ectopic expression of p2 induced by CI alleles could be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because phlobaphene pigment accumulation is correlated with kernel pericarp thickness and reduced mycotoxin contamination on maize kernels (Landoni et al 2020), the ectopic expression of p2 induced by CI alleles could be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the target p1/p2 locus plays a central role in regulating phlobaphene biosynthesis in maize tissues ( Grotewold et al 1994 ). Because phlobaphene pigment accumulation is correlated with kernel pericarp thickness and reduced mycotoxin contamination on maize kernels ( Landoni et al 2020 ), the ectopic expression of p2 induced by CI alleles could be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated a direct correlation between phlobaphene accumulation and kernel pericarp thickness, as well as reductions in mycotoxin contamination on maize kernels. Therefore, the ectopic expression of p2 induced by CI alleles could be beneficial to the plants (Landoni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The phlobaphene pigments controlled by the maize p1 gene are non-essential, and many modern corn varieties lack significant kernel pericarp color. However, a recent study reported that high phlobaphene levels were associated with increased kernel pericarp thickness and reduced mycotoxin contamination when compared to isogenic colorless pericarp lines lacking an active p1 gene (Landoni et al 2020). Because the p1 and p2-encoded proteins are highly similar and regulate the same flavonoid biosynthetic pathway (Zhang P. et al 2000), similar effects are likely induced by the expression of p2 in the pericarp.…”
Section: Effects Of Inversions On Fitnessmentioning
confidence: 99%